Reply. Issue 4 (2nd February 2022) - Harada, Jumpei; Nagata, Kazuma; Morimoto, Takeshi; Iwata, Kentaro; Matsunashi, Atsushi; Sato, Yuki; Tachikawa, Ryo; Ishikawa, Akira; Tomii, Keisuke
Abstract : See related Letter